Interplay between DNA polymerases ß and λ in repair of oxidation DNA damage in chicken DT40 cells - Tano, Keizo (2007)
DNA polymerase λ (Pol λ) is a DNA polymerase β (Pol β)-like enzyme with both DNA synthetic and 5'-deoxyribose-5'-phosphate lyase domains. Resent biochemical studies implicated Pol λ as a backup enzyme to Pol ß in the mammalian base excision repair (BER) pathway. To examine the interrelationship between Pol λ and Pol ß in BER of DNA damage in living cells, we disrupted the genes for both enzymes either singly or in combination in the chicken DT40 cell line and then characterized BER phenotypes. Disruption of the genes for both polymerases caused hypersensitivity to H(2)O(2)-induced cytotoxicity, whereas the effect of disruption of either polymerase alone was only modest. Similarly, BER capacity in cells after H(2)O(2) exposure was lower in Pol β(−/−)/Pol λ(−/−) cells than in Pol β(−/−), wild-type and Pol λ(−/−) cells, which were equivalent. These results suggest that these polymerases can complement for one another in counteracting oxidative DNA damage. Similar results were obtained in assays for in vitro BER capacity using cell extracts. With MMS-induced cytotoxicity, there was no significant effect on either survival or BER capacity from Pol λ gene disruption. A strong hypersensitivity and reduction in BER capacity was observed for Pol β(−/−)/Pol λ(−/−) and Pol β(−/−) cells, suggesting that Pol β had a dominant role in counteracting alkylation DNA damage in this cell system.